Leitura para a dimensão material e a Stimmung : uma noite nos shows de Heavy Metal Cristão - Coradini, Ângela Mastella (2013)
Proposition production of presence (Gumbrecht 2010), the notion of Stimmung (Gumbrecht 2009) and Heavy Metal Christian (HMC) are the pillars of this dissertation. The tension in the aesthetic, the shows, the environments and music of the HMC directs us to a place where Christians and secular elements coexist. In Christian Heavy Metal concerts, the greatest expression of the musical genre, the sounds, the colors, the smells, temperatures, objects, facial expressions and body mingle composing a Stimmung (atmosphere) peculiar pulse and tension sacral profane. We propose to think this dissertation movements "of desinterdição mundanities" performed by a few strands of Christianity and that permeate the HMC, the expansion of materiality that delimit the HMC, and Stimmung that touches and engages the bodies.